Sustainable development at risk - Hulse, Joseph H. (Bangalore, 2007)
Over the past half century, the idea of sustainable development has evolved and rooted itself in the lexicon on international development. But what is it, really? Are development agencies truly committed to long-term sustainable solutions to development issues? Are we learning from our past successes and failures? This book takes an historical perspective on these questions. The analysis begins with the Atlantic Charter, the creation of the United Nations, its family of agencies, and the international development banks. It reviews recommendations from international commissions and conferences, from World bank and UNDP development reports. It comments on governmental policies, human and industrial actions detrimental to the planet's environment and natural resources. It studies the patterns by which biotechnologies essential to human survival and health have progressed over the past 8,000 years, and the consequences of uncontrolled urban growth on food and health security.
Keywords: Sustainable development